Factors influencing the pursuit of a Master's degree in library and information science - Sagun, Karryl Kim A.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
There are very few literature on the pursuit of a master's degree in library and information science, and much lesser are those in the Philippine setting. In this regard, this study was made to focus on the factors influencing the pursuit of the said degree, according to the responses of MLIS students of the UP ILIS.
Sixty-one students were surveyed, and this consisted of 100 of those attending classes during the two-week data gathering period. Twenty-two of the respondents are in Plan A, 38 are in Plan B, while one person did not disclose the curriculum, he is enrolled in.
The data gathered from the survey questionnaires showed that disparity among the responses of Plan A and Plan B students is great with regard to their profile. However, responses on the factors that influenced them almost had the same trend all throughout.
There is a high computed mean for the external-professional and internally- psycho-social sub-factors, which both caters to events that are anticipated to take place after graduation. There is a very low computed mean for the internal-personal factors and external-LIS promotional factors, which can denote that those factors does not have that much weight on the decisions of a graduate student, particularly the opinions of his/her family.
Recommendations included strengthening of the curriculum, promotion of other tracks (other than IT), and promotion of MLIS to those taking up BLIS.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines School of Library and Information Studies -- Degrees; Library education (Continuing education) -- Philippines